Perubahan Bentuk pada Perambatan Signal Bi-kromatik dan Pengaruhnya terhadap Amplitudo Maksimum - Marwan Marwan; Andonowati Andonowati (Institut Teknologi Bandung, 2003)
We consider the signal propagation from a wave generation often simulated in hydrodynamic laboratories. As a particular case, we will study a deformation from the evolution of a bi-chromatic signal. The signal is a superposition of two mono-chromatics with different of frequencies. We use a KdV equation with exact dispersion as a model for uni-directional surface gravity waves. Using a direct expansion in the form of power series of the elevation signal amplitude gives a result to resonance in the third order. We correct this expansion using a modified Linstead-Poincare technique. From this, a non linear dispersion relating the wave number, amplitude and frequency can be derived. If the frequency different between the two mono-chromatics forming the bi-chromatics signal is small then the effect of third order side bands can dominate the second order terms. The coefficient of these terms contain an expression in the form of ()2/Îºqq. Deformations of bi-chromatic signal are significantly effected by this non linear dispersion as well as the side band terms. In this paper we will study the deformation of bi-chromatic signal propagation through the new approach called Maximal Temporal Amplitude (MTA).